A review of gut microbiota as a therapeutic approach for Parkinson’s disease - Debosree Ghosh; Suvendu Ghosh; Madhurima Sharma; Sutapa Datta (MGM Journal of Medical Sciences)
Parkinson’s disease (PD) is a neurodegenerative disorder that affects the brain–gut axis, manifesting through both motor dysfunction and nonmotor symptoms. While several factors contribute to PD, the precise cause remains unknown. Research studies suggest that an altered gut microbiota (GM) plays a key role in PD pathophysiology. Gut dysbiosis compromises the integrity of the intestinal epithelium, increasing gastrointestinal permeability. This, in turn, activates the innate immune system, leading to systemic inflammation, whereas the adaptive immune system responds to bacterial proteins through cross-reactivity with human antigens. The altered GM promotes the accumulation of alpha-synuclein fibrils in the intestinal neural plexus, which are then transported to the central nervous system, driving the core pathological process of PD. This review focuses on the connection between gut dysbiosis, PD pathology, and current microbial-based therapeutic interventions. Furthermore, research into innovative approaches to modulate the GM and reinforce gut epithelial integrity is crucial to halting or slowing PD progression.